Wilms Tumor 1 Mutations Are Independent Poor Prognostic Factors in Pediatric Acute Myeloid Leukemia - Wang, Yin; Weng, Wen-Jun; Zhou, Dun-Hua; Fang, Jian-Pei; Mishra, Srishti; Chai, Li; Xu, Lu-Hong (Frontiers in Oncology, 2021)
The prognostic impact of Wilms tumor 1 (WT1) mutations remains controversial for patients with acute myeloid leukemia (AML). Here, we aimed to determine the clinical implication of WT1 mutations in a large cohort of pediatric AML. The clinical data of 870 pediatric patients with AML were downloaded from the therapeutically applicable research to generate effective treatment (TARGET) dataset. We analyzed the prevalence, clinical profile, and prognosis of AML patients with WT1 mutations in this cohort. Our results showed that 6.7% of total patients harbored WT1 mutations. These WT1 mutations were closely associated with normal cytogenetics (P<0.001), FMS-like tyrosine kinase 3/internal tandem duplication (FLT3/ITD) mutations (P<0.001), and low complete remission induction rates (P<0.01). Compared to the patients without WT1 mutations, patients with WT1 mutations had a worse 5-year event-free survival (21.7±5.5% vs 48.9±1.8%, P<0.001) and a worse overall survival (41.4±6.6% vs 64.3±1.7%, P<0.001). Moreover, patients with both WT1 and FLT3/ITD mutations had a dismal prognosis. Compared to chemotherapy alone, hematopoietic stem cell transplantation tended to improve the prognoses of WT1-mutated patients. Multivariate analysis demonstrated that WT1 mutations conferred an independent adverse impact on event-free survival (hazard ratio 1.910, P = 0.001) and overall survival (hazard ratio 1.709, P = 0.020). In conclusion, our findings have demonstrated that WT1 mutations are independent poor prognostic factors in pediatric AML.